Francisco MORALES LOMAS (ed.).— La narrativa elocuente de Antonio Muñoz Molina. Bruselas et al.: Peter Lang, 2021, 248 pp. - García Cueto, Pedro (Signa: Revista de la Asociación Española de Semiótica, 2023)
Reseña